PENGUATAN NILAI-NILAI THORIQOH BERBASIS QUR’ANI: Strengthening the Values of Thoriqoh Based on the Qur'an - ., Sunardi; Munfarida, Isah; Hasan, Moch. Sya’roni; ., Solechan (Al-Amal: Jurnal Pengabdian Masyarakat, 2024)
The assistance in strengthening Thoriqoh values based on the Qur'an is a strategic effort to build spiritual character rooted in Islamic principles. This study aims to analyze the effectiveness of assistance in instilling Thoriqoh values aligned with Qur'anic teachings in specific communities. A qualitative approach with descriptive methods was employed through observations, interviews, and focus group discussions (FGD). The assistance was conducted in several stages, including value awareness, habituation practices, and sustainability evaluations. The findings indicate that a Qur'anic approach in Thoriqoh practices enhances participants' understanding of core Islamic values such as sincerity (ikhlas), patience (sabr), reliance on Allah (tawakkul), and love for Allah (mahabbah). Additionally, this approach strengthens participants' spiritual connection with the Qur'an by integrating relevant verses into each Thoriqoh practice. This study recommends a Qur'anic-based assistance model as an alternative for developing Islamic character that is practical and sustainable, especially in Islamic boarding schools (pesantren) and religious communities